2015
DOI: 10.3109/09637486.2015.1007451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of industrial freezing on the stability of chemopreventive compounds in broccoli

Abstract: Broccoli (Brassica oleracea L. var. Italica) is largely consumed all over the world and has a high economic importance. Likewise, broccoli contains high levels of glucosinolates, carotenoids and total phenols, which are related with the prevention of chronic diseases. The present project's objective was to evaluate the effect of industrial freezing on the stability of bioactive molecules in seven commercial broccoli cultivars (Tlaloc®, Endurance®, Florapack®, Domador®, Steel®, Iron Man® and Avenger®). In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Previous study reported that freezing slightly increased the chlorophyll content of plant food (Alanis-Garza, Becerra-Moreno, Mora-Nieves, Mora-Mora, & Jacobo-Velazquez, 2015). On the basis of our study, it can be pointed out that pre-freezing processing and freezing handling resulted in a statistically significant elevation of chlorophyll content, which was mainly caused by blanching process.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous study reported that freezing slightly increased the chlorophyll content of plant food (Alanis-Garza, Becerra-Moreno, Mora-Nieves, Mora-Mora, & Jacobo-Velazquez, 2015). On the basis of our study, it can be pointed out that pre-freezing processing and freezing handling resulted in a statistically significant elevation of chlorophyll content, which was mainly caused by blanching process.…”
Section: Discussionmentioning
confidence: 90%
“…Broccoli is subjected to processing including cutting, washing, blanching and cooling prior to freezing. Although several studies have demonstrated that contents of glucosinolates and main antioxidants in broccoli were affected by post-harvest processing such as cooking (Yuan, Sun, Yuan, & Wang, 2009), blanching (Cieślik, Leszczyńska, Filipiak-Florkiewicz, Sikora, & Pisulewski, 2007;Nugrahedi, Verkerk, Widianarko, & Dekker, 2015), and freezing (Alanis-Garza, Becerra-Moreno, Mora-Nieves, Mora-Mora, & Jacobo-Velazquez, 2015;Cieślik, Leszczyńska, Filipiak-Florkiewicz, Sikora, & Pisulewski, 2007), little is known about the dynamics of main bioactive compounds in broccoli during pre-freezing processing, namely cutting, washing, blanching, cooling, and freezing handling period.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [27] reported an increase (about 21 %) of β-carotene in broccoli during frozen storage compared to the raw and blanched material. In the study of Alanís-Garza et al [38] broccoli subjected to industrial freezing showed higher levels of total carotenoids (~60-300 % higher) as compared with fresh broccoli. The authors suggest that bioactive compounds in frozen broccoli would be more bioavailable than in raw.…”
Section: β-Carotenementioning
confidence: 93%
“…Because of the disnatured myrosinase, blanch-frozen broccoli can retain the same levels of glucosinolates after 90 days of frozen (À20 C) storage [194]. Furthermore, Alanís-Garza et al [195] reported that glucosinolate content increased in three tested broccoli cultivars while remained constant in only one cultivar after blanching and freezing. In order to maximize the production of cancer preventative sulforaphane in broccoli florets, blanching step is optimized to maintain myrosinase activity while destroying ESP activity, for a high percentage of glucoraphanin can be converted to a nitrile with ESP as mentioned above.…”
Section: Blanch-freezingmentioning
confidence: 97%